An overview of Beauty Standards as culturally projected within Ghana’s Most Beautiful Pageant - Azuah, Scholastica Wompakeah; J. , Adu-Agyem; A., Eric Appau (Archives of Business Research, 2020)
Beauty pageants such as Ghana’s Most Beautiful (GMB) normally select a lady to serve as a symbolic representation of their collective identity to a larger audience. The common tastes including fashion and lifestyle of members of a society collectively form and represent the tastes and lifestyle of its people; therefore the fashion and culture of a particular time symbolize the spirit of the times. Cultural principles refer to the cultural values that are categorized, organized and evaluated in each society. The principles governing standards in one region or country may not be same for other places. For example, the reasons for wearing of beads in one region may differ from that of other regions in Ghana. Standards are held to when they are documented and subsequently in line with cultural values. In a discussion with two members of the GMB organizing team during a national audition at TV3 premises in August 2017, they admitted that there was no comprehensive policy document spelling out beauty standards and guidelines of the pageant. The research adapts a sequential exploratory design with a population made up of all participants of GMB. The purpose of the study was to find out the beauty standards of GMB pageant as culturally projected within the beauty pageant. It was found out that the pageant occasionally deviates from its main focus of projecting Ghanaian cultural values. It should therefore regularly refer to its objectives while exhibiting all its activities.